Case series on silvery hair syndromes: Single center experience - Sirisharani Siddiahgari; Santosh Kumar Soma; Chandravathi Penmetcha; Sandhya Vaddadi; Varshini Bandi; Lokesh Lingappa (Wolters Kluwer Medknow Publications, 2022)
Background: Silvery Hair Syndromes (SHS), an autosomal recessive inherited disorder, includes Chediak-Higashi syndrome (CHS), Griscelli syndrome (GS), Hermansky-Pudlak syndrome (HPS), and Elejalde syndrome. Associated immunological and neurological defects and predilection for hemophagocytic lymphohistiocytosis (HLH) makes them a distinctive entity in pediatric practice. Thorough clinical examination, bedside investigations such as peripheral blood smear (PBS) and hair microscopy, and bone marrow (BM) examination are inexpensive and reliable diagnostic tools. Methods: We report 12 cases with SHS (CHS, n = 06; GS, n = 04; HPS, n = 02). Results: 8 out of 12 SHS children (CHS-05, GS-03) presented with HLH. Out of 5 cases of CHS with HLH, 2 died, 3rd is stable post-chemotherapy; 4th completed chemotherapy, underwent matched related hematopoietic stem cell transplant (HSCT), and is stable 8 months off treatment. The 5th child completed chemotherapy and is in process of transplant. One CHS child without HLH is thriving without any treatment. Of the 4 GS cases, 3 presented with HLH and received chemotherapy (HLH 2004 protocol). One lost follow-up after initial remission; another had recurrence 7 months off treatment and discontinued further treatment. The third child had recurrence 1.5 years after initial chemotherapy; HLH 2004 protocol was restarted followed by HSCT from matched sibling donor; is currently well, 2.5 years post-transplant. One child with GS had neurological features with no evidence of HLH and did not take treatment. Of 2 children with HPS, one presented with severe sepsis and the other with neurological problems. They were managed symptomatically. Conclusion: In SHS with HLH, chemotherapy followed by allogeneic hematopoietic stem cell transplantation is a promising curative option.